Punishment dalam Modifikasi Perilaku di SMK Negeri 1 Sungailiat - Dhealivenda, Cahya (Department of Islamic Guidance and Counseling, 2023)
In essence every individual has a soul, which in this case is like the body, if it is too pampered, it will not be able to withstand a tiring hard work and an insurmountable difficulty. Therefore, punisment needs to exist in life and the world of education. The purpose of this study is to explore data Knowing information related to punishment in SMK Negeri 1 Sungailiat. The research method used is an interview where the data collection method involves direct interaction between the researcher and the subject and method documentasi. From the results obtained from the interview, it was stated that punishment helped students at SMK Negeri 1 Sungailiat become more disciplined in terms of entering class on time, dress code, and schoolwork. Punishment given in the form of helping students to get a deterrent effect for making mistakes, has a good impact on students. Because most students no longer want to make the same mistake because they don't want to get punishment, although sometimes there are student statements that may not get a deterrent effect from the punishment given.